Butyrolactones and Diketopiperazines from Marine Microbes: Inhibition Effects on Dengue Virus Type 2 Replication - Lin, Chun-Kuang; Wang, Yu-Ting; Hung, Er-Mao; Yang, Yu-Liang; Lee, Jin-Ching; Sheu, Jyh-horng; Liaw, Chih-Chuang (Planta Medica, 2017)
Two new compounds, 4S,10R-dihydroxy-11-methyl-dodec-2-en-1,4-olide (1) (butyrolactone-type) and cyclo-(4-trans-6-dihydroxy-proline-D-leucine) (2) (diketopiperazine-type), as well as one known 4S,10-dihydroxy-10-methyl-dodec-2-en-1,4-olide (3) and three known diketopiperazines, cyclo-(L-proline-L-leucine) (4), cyclo-(4-trans-hydroxy-L-proline-L-leucine) (5), and cyclo-(4-trans-hydroxy-L-proline-L-phenylalanine) (6), were isolated from the ethyl acetate extracts of Streptomyces gougerotii GT and Microbulbifer variabilis C-03. Compounds 3, 4, 5, and 6 exhibited a significant reduction effect on dengue virus type 2 replication with EC50 values of 21.2, 16.5, 12.3, and 11.2 µM, respectively.
Keywords: Streptomyces gougerotii; Streptomycetaceae; Microbulbifer variabilis; Alteromonadaceae; Butyrolactone; diketopiperazine; dengue virus type 2 replication